2005
DOI: 10.1007/s11284-005-0052-y
|View full text |Cite
|
Sign up to set email alerts
|

The production‐to‐respiration ratio and its implication in Lake Biwa, Japan

Abstract: Production-to-respiration (P:R) ratio was estimated at an offshore site of Lake Biwa in order to examine whether the plankton and benthic community is subsidized with allochthonous organic carbon, and to clarify the role of this lake as potential source or sink of carbon dioxide. The respiration rate of protozoan and metazoan plankton was calculated from their biomass and empirical equations of oxygen consumption rates, and that of bacterioplankton was derived from their production rate and growth efficiency. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Similar seasonal variation in F assim + F denit of showing a maximum value in summer and a minimum value in winter was detected in Lake Mashu as well (Tsunogai et al ). Past observations on primary production rates in Lake Biwa ( F assim ) also displayed similar seasonal variation (Yoshimizu et al ; Urabe et al ; Ota et al ). Thus, the observed seasonal variation in F assim + F denit , showing a maximum in summer and a minimum in winter, is a highly reasonable estimate for this lake.…”
Section: Resultssupporting
confidence: 59%
“…Similar seasonal variation in F assim + F denit of showing a maximum value in summer and a minimum value in winter was detected in Lake Mashu as well (Tsunogai et al ). Past observations on primary production rates in Lake Biwa ( F assim ) also displayed similar seasonal variation (Yoshimizu et al ; Urabe et al ; Ota et al ). Thus, the observed seasonal variation in F assim + F denit , showing a maximum in summer and a minimum in winter, is a highly reasonable estimate for this lake.…”
Section: Resultssupporting
confidence: 59%
“…Small lakes can depend on allochthonous DOC for metabolic activities (Wetzel 1984(Wetzel , 1995Urabe et al 2005;Wetzel & Tuchman 2005). Lake Phewa has a small volume relative to its catchment area, and the monsoondominated climate can deliver up to 4846 mm of rainfall per year (Paudel & Thapa 2001;Gurung et al 2006), causing lake water to be exchanged many times during summer (Ferro 1981(Ferro ⁄ 1982Lohman et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Small lakes can depend on allochthonous DOC for metabolic activities (Wetzel 1984, 1995; Urabe et al. 2005; Wetzel & Tuchman 2005).…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that organic matter resuspended by strong winter mixing of the water column may have supported zooplankton growth. Although such a hypothesis still remains to be tested, Urabe et al (2005) showed that an allochthonous source of organic carbon is not negligible in the support of the Lake Biwa pelagic system, especially in winter. Rotifers were abundant in late winter just before large zooplankton increased as in the PEG model, but they were scarce in summer since large zooplankton were abundant in contrast to the pattern in the PEG model, probably due to low fish predation in this lake.…”
Section: Temporal and Spatial Aspects Of Dynamics In Natural Populationsmentioning
confidence: 99%